Degradation of Cypermethrin by Indigenous Bacteria from Contaminated Soil - Indratin, Indratin; Kurnia, Asep; Wahyuni, Sri (Makara Journal of Science, 2019)
Soil contamination by pesticides should be controlled by using soil microbes with the ability to degrade pesticide resi-dues. Microorganisms that have adapted to a particular pesticide could accelerate the degradation process. The present study aimed to select bacteria in soil that could potentially degrade cypermethrin residues. Experiments were carried out in a laboratory and employed soil samples collected from the districts of Demak, Magelang, and Brebes. Each soil sample was initially tested for the presence of bacteria and pesticide residues. Indigenous microbes capable of living in contaminated environments were adapted to cypermethryn and cultured in the laboratory. Experiment was carried out in several stages, namely, (1) isolation and identification of microbes that could degrade cypermethrin, (2) testing of the growth characteristics of isolates in cypermethrin, and (3) determination of cypermethrin residues in cultures. Three isolates, namely Pseudomonas alcaligenes, Bacillus amyloliquenfaciens, and Pseudomonas aeruginosa, were found to decrease cypermethrin residues by up to 95% with fast half-lives and good growth capability. The results demonstrate the potential applications of the isolates in biodegradation processes and remediation of cultivation fields.